The impact of different housing systems during pregnancy on the development of the offspring of sheep in the UK - Valente, Leonor (2018)
Studies across different species have demonstrated that maternal stress during pregnancy can affect offspring development and welfare, both at the physiological and behavioural level. Throughout pregnancy, domestic livestock may experience various stressors that can inhibit health and productivity, and consequently impact on the development of the offspring. Several of these relate to the gestational social environment, a subject that has not received much attention from a prenatal stress perspective. In the UK, approximately half of ewes are housed prior to lambing. As a consequence, factors such as social instability, high stocking density, dog exposure and unpredictable feeding schedule have been identified as potential stressors for housed sheep. Some of these impose a degree of competition for resources while others expose the pregnant ewes to an uncertain and unpredictable environment. This project aimed to investigate the potential effect of these aspects of ewe husbandry when applied during pregnancy on lamb behaviour and welfare. The first experiment investigated the effects of the legally maximum stocking density and social mixing during pregnancy on the offspring. The second experiment looked at the effects of three different levels of maternal stress on the offspring, which included a higher stress environment where ewes were exposed to a dog, the feeding schedule was unpredictable and stocking density was the maximum allowed legally; a medium stress environment where there was no dog exposure and feeding schedule was predictable but stocking density was kept the same; and a lower stress environment with lower stocking density, ad libitum feed and no dog exposure. Lambs were followed from birth to slaughter and the effects of these potential maternal stressors on lamb behaviour and factors related to survival, immunity, growth, and epigenetic regulation of neuroendocrine stress axis function were investigated. The maternal stressors had very subtle impact on lamb behaviour and growth but birth weight and immunity were not affected. However, effects of prenatal treatment were found on brain morphology and factors regulating stress axis activity. Therefore there seems to be no major implications for lamb welfare of these maternal stressors. Hence, from a farm management perspective this study suggests that, in general, current ewe management practices in the UK are not detrimental for lamb welfare.